Puzzle resolution: chest pain - Nikpoor, S (Iran University of Medical Sciences, 1995)
Most of the patients imagine that chest pain is not sign of heart attack. But, may be pain is not sign of heart attack. Pain source may be from pulmonary, stomach, intestinal, psychologic or musculoskeletal problems. From these factors, when two or more factors combine to each other, similar signs are happen. All of these factors harden diagnosis of chest pain reason. Only with separation of personal signs and related diseases can draw clear diagnostic image. Patient's subjective evaluation of pain, his/her appearance, attitude, mentions and health must be assessing. When we perform history taking, we must be attend to interpretation of severity, site, duration and quality of patient's pain. Is he/she using words such as "tearing" and "stabbing" that showing pneumothorax?  Is he/she using words such as "crusher pain" that is sign of esophageal spasm? Is he/she saying that has feeling of asphyxia or nearing death? Is he/she compressing his/her chest with his/her hands or fist? It is may be due to coronary artery spasm and angina pectoris